Influence of stiffness constant of stern bearing on vibration and acoustic radiation of whole submarine - WANG Lucai (Zhongguo Jianchuan Yanjiu, 2018)
[Objectives] This paper studies the influence of the stiffness constant of a stern bearing on the vibration and acoustic radiation of a whole submarine.[Methods] Based on the form of SUBOFF, a whole submarine model is established in which the structures of the propeller and shaft are first formed in solid elements. Through calculating and comparing the structural vibration and acoustic radiation driven by a vertically excited force, the influence of the elastic coefficient of the stern bearing on the vibroacoustic of the overall submarine structure is mainly considered. [Results] It is demonstrated that the reduction of the elastic coefficient of the stern bearing leads to the convergence of structural vibration and acoustic radiation to the second order overall bending modal frequency, and the frequency gradually becomes lower, which can benefit the vibroacoustic reduction of submarines at frequencies higher than the second order overall bending modal frequency. [Conclusions] These results provide a reference for the acoustic design of submarine structures.